Vocalizations of Scinax dolloi (Anura, Hylidae) at its type locality Vila de Maringa, Itatiaia, Rio de Janeiro, Brazil, including bioacoustic comparisons with morphologically similar species - Santos, Lucas Rodrigo dos [UNESP]; Silva, Paulo Henrique [UNESP]; Martins, Itamar Alves (Soc Brasileira Herpetologia, 2021)
This study presents the description of the advertisement call and a second call type of Scinax dolloi, recorded at its type locality, Vila de Maringa, ltatiaia, in the State of Rio de Janeiro, southeastern Brazil. The advertisement call consists of a multi-pulsed note showing upward modulation in the initial pulses. The second call type is usually emitted between advertisement call notes and consists of a modified version of the advertisement call with juxtaposition of the pulses that form the note in its structure. The advertisement call pulse rate, number of pulses and note duration best differentiate Scinax dolloi, S. hayii, and S. perereca. Despite some overlap in the spectral components (frequency range and dominant frequency), the three species present significantly different means.
Keywords: Acoustic discrimination; bioacoustics; Scinaxinae; southeastern Brazil; vocalization